Peran Media Pembelajaran dalam Mata Pelajaran Matematika di Sekolah Dasar - Desi Mauliana; Adrias Adrias; Fadila Suciana (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Learning media has a crucial role in the educational process, especially in mathematics subjects at the elementary school level. The use of learning media aims to increase students' interest and enthusiasm in learning, as well as potentially improve their learning outcomes. Learning that utilizes learning media tends to be more interesting and easier to understand than learning methods that are monotonous and do not involve media. This study aims to conduct a literature review on the role of learning media in the context of mathematics learning in elementary schools. The research method used is a literature study, focusing on research articles published between 2020 and 2025. The analyzed articles come from accredited national journals accessed through Google Scholar with the help of the Publish or Perish application. The findings of this study show that the use of learning media in mathematics subjects has a significant impact on increasing students' interest in learning, motivation, and learning outcomes. In addition, learning media also functions to facilitate the understanding of concepts and provide direct experience to students related to the material taught.